A new species of Namib Day Gecko (Gekkonidae: Rhoptropus Peters, 1869) from the Serra da Neve inselberg, southwestern Angola - Parrinha, Diogo; Marques, Mariana P.; Tiutenko, Arthur; Heinicke, Matthew P.; Bauer, Aaron M.; Ceríaco, Luis M.p. (Zootaxa, 2025)
The genus Rhoptropus comprises nine recognized species of diurnal geckos endemic to the arid regions of Angola and Namibia. Seven species occur in Angola, including the widespread R. boultoni and the poorly known Angolan endemics R. benguellensis and R. montanus, formerly recognized as subspecies of R. boultoni. While R. benguellensis is relatively widespread in the Angolan Escarpment highlands, R. montanus is geographically restricted to the Huíla Plateau. Recent fieldwork on the Serra da Neve inselberg, a herpetological diversity hotspot in southwestern Angola, revealed the presence of an undescribed species of Rhoptropus at an elevation of approximately 1600 m. An integrative taxonomic approach combining coloration, morphological and molecular data supports the recognition of this population as a distinct taxonomic unit with affinities to R. montanus, which we describe herein as Rhoptropus nivimontanus sp. nov. The discovery of a new species of Rhoptropus endemic to Serra da Neve is discussed in the biogeographic context of the region.